2018
DOI: 10.1007/s00402-018-2992-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between spinal sagittal alignment and acetabular coverage: a patient-matched control study

Abstract: The SS and LL were greater in patients with DDH than in patients with hip pain, but without DDH. Patients with DDH might show lumbar hyperlordosis to rotate the pelvis anteriorly, increasing the anterosuperior acetabular coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
2
32
0
5
Order By: Relevance
“…We know of no other studies that describe the reversible changes in the pelvis after bilateral PAO. Previous work by Fukushima et al [8] compared the sagittal vertical axis, pelvic tilt, pelvic incidence, sacral slope, and lumbar lordosis in patients with acetabular dysplasia (defined by LCEA < 20°) and patients with symptomatic labral tears. They found a higher sacral slope and lumbar lordosis in patients with dysplasia and no difference in pelvic tilt between the two study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know of no other studies that describe the reversible changes in the pelvis after bilateral PAO. Previous work by Fukushima et al [8] compared the sagittal vertical axis, pelvic tilt, pelvic incidence, sacral slope, and lumbar lordosis in patients with acetabular dysplasia (defined by LCEA < 20°) and patients with symptomatic labral tears. They found a higher sacral slope and lumbar lordosis in patients with dysplasia and no difference in pelvic tilt between the two study populations.…”
Section: Discussionmentioning
confidence: 99%
“…When the acetabulum is deficient anteriorly, we speculate that patients attempt to compensate for this anterior deficiency by involuntarily increasing their anterior pelvic tilt. Recently, Fukushima et al [8] evaluated radiographic parameters of sagittal alignment in patients with hip pathology and noted an increased lumbar lordosis and sacral slope in patients with acetabular dysplasia when compared with patients with symptomatic labral tears. Matsuyama et al [14] observed a similar pattern with an increase in anterior pelvic tilt and a compensatory hyperlumbar lordosis in patients with bilateral congenital hip dislocation secondary to dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Theoretically, the acetabular morphology has less impact on the sagittal tilt of the pelvis, while some studies reported that DDH patients tilt the pelvis anteriorly in standing to compensate for insufficient femoral head coverage by the dysplastic acetabulum. [14][15][16] On the other hand, others found a posterior rotation of the pelvis occurring from the supine to the standing position. 17 Controversy remains regarding whether compensation due to insufficient femoral head coverage is accompanied by a postural change in DDH patients.…”
mentioning
confidence: 99%
“…As the dynamics of the spine–pelvis–hip construct, the pelvis is controlled by two hinges, posteriorly the lumbosacral joint and anteriorly the hip joint . Theoretically, the acetabular morphology has less impact on the sagittal tilt of the pelvis, while some studies reported that DDH patients tilt the pelvis anteriorly in standing to compensate for insufficient femoral head coverage by the dysplastic acetabulum . On the other hand, others found a posterior rotation of the pelvis occurring from the supine to the standing position .…”
mentioning
confidence: 99%
“…Therefore, DDH patients might develop a compensatory anterior inclination of the pelvis so that an approximation of the acetabular cup for the femoral head can be achieved. Fukushima et al showed that DDH patients with increased PI had higher sacral slope (SS), which was considered to compensate for increased anterior acetabular coverage [ 24 ]. Thus, to increase acetabular coverage, a increased PI may be overdeveloped to provide sufficient sagittal balance in DDH patients.…”
Section: Discussionmentioning
confidence: 99%